Anthropogenic hybridization between endangered migratory and commercially harvested stationary whitefish taxa (Coregonus spp.). (8th July 2014) - Dierking, Jan; Phelps, Luke; Præbel, Kim; Ramm, Gesine; Prigge, Enno; Borcherding, Jost; Brunke, Matthias; Eizaguirre, Christophe
Abstract Natural hybridization plays a key role in the process of speciation. However, anthropogenic (human induced) hybridization of historically isolated taxa raises conservation issues. Due to weak barriers to gene flow and the presence of endangered taxa, the whitefish species complex is an excellent study system to investigate the consequences of hybridization in conservation. We focused on three naturally reproductively isolated whitefish taxa in Germany: the endangered, anadromous North Sea houting (NSH) and Baltic houting (BH), which were reintroduced after local extinction, and the commercially stocked European whitefish (EW). To evaluate the genetic integrity of each taxon, source and reintroduced populations of NSH and BH, and EW populations were characterized based on two mitochondrial and 17 microsatellite loci. Additionally, we investigated gill raker counts as an adaptive phenotypic trait. Even though clear genetic and phenotypic differentiation confirmed the houtings as separate evolutionarily significant units, admixture analyses revealed an extensive hybrid zone. Hybridizations were introgressive, positively correlated with genetic diversity, and were reflected in the gill raker counts. The BH distribution range showed higher heterogeneity and stronger admixture than the NSH range. Erroneous stocking with non‐native genotypes best explained these patterns, which pose challenges for the conservation of the endangered NSH and BH.